Treatment of dragonfruit ( Hylocereus polyrhizus ) with salicylic acid and methyl jasmonate improves postharvest physico-chemical properties and antioxidant activity during cold storage - Mustafa, Maysoun A.; Ali, Asgar; Seymour, Graham B.; Tucker, Gregory A. (Elsevier, 2018)
As the market for tropical fruit constantly expands, cold storage is increasingly used for transporting fruits over long distances. This is an economic postharvest tool, yet challenges tropical fruits by exposure to chilling injury. An assessment of the effect of abiotic stresses, induced by cold storage, on dragonfruit was conducted. Dragonfruit was treated with salicylic acid (SA) and methyl jasmonate (MJ) and subjected to cold storage for three weeks. Fruits were treated with either SA or MJ, administered at four different concentrations, along with an untreated control, and stored at 6 °C. Changes in biochemical quality parameters, along with bioactive content and antioxidant activity were assessed during storage. Application of SA was found to reduce the metabolic activity of the fruit, as determined by soluble solids content and titratable acidity. Meanwhile, MJ significantly enhanced the betacyanin content and antioxidant activity. We demonstrate that cold storage can be applied for dragonfruit, by combining the treatment with the application of hormones, especially MJ which can enhance the antioxidant activity of dragonfruit under cold storage.